A 30-Year Climatological Analysis of Atmospheric Dynamics Anomalies during CENS in Western Indonesia - Didik Kurniawan; Farhan Oktaviansyah Hidayat; Binsar Hakim Aritonang; Rizki Addriyan Aliyafi; Sayful Amri (Journal of Maritime Policy Science, 2025)
Cross Equatorial Northerly Surges or CENS are an important atmospheric phenomenon influencing weather variability over the Maritime Continent. These surge events frequently generate hazardous hydrometeorological conditions, including heavy rainfall and surface cooling, posing risks to maritime activities and coastal regions. This study presents a climatological analysis of atmospheric dynamics anomalies associated with CENS over the Western Maritime Continent using a 30 year dataset covering the period from 1991 to 2020. Atmospheric anomalies in precipitation rate, outgoing longwave radiation, relative humidity, and maximum temperature are analyzed using NCEP NCAR Reanalysis data. Active CENS events are identified based on meridional wind speed thresholds during the boreal winter season from November to March, resulting in 170 active CENS days. The results indicate that CENS events are consistently associated with enhanced precipitation, reduced outgoing longwave radiation, increased low level relative humidity, and widespread surface cooling. These anomalies reflect intensified convective activity driven by the transport of cold and moist air masses from the Northern Hemisphere. Maximum temperature decreases by up to 4.5 degrees Celsius due to the combined effects of cold air advection and increased cloud cover that suppresses incoming solar radiation. By adopting a multi decadal climatological framework, this study provides new insights into persistent atmospheric responses to CENS that are not fully captured by shorter term or event based analyses. The climatological baseline established here improves understanding of large scale drivers of extreme rainfall and atmospheric instability over western Indonesia and offers valuable information for enhancing weather forecasting, early warning systems, and maritime risk management.